TBA trading and liquidity in the agency MBS market - James Vickery; Joshua Wright (Federal Reserve Bank of New York, 2010)
Most mortgages in the United States are securitized through the agency mortgage-backedsecurities (MBS) market. These securities are generally traded on a 'to-be-announced,' or TBA, basis. This trading convention significantly improves agency MBS liquidity, leading to lower borrowing costs for households. Evaluation of potential reforms to the U.S. housing finance system should take into account the effects of those reforms on the operation of the TBA market.
Keywords: G21; G12; G19; 330; Mortgage-backed securities; TBA trading; liquidity; adverse selection